The Meaning of Media : Texts and Materiality in Medieval Scandinavia - Blennow, Anna; Hedström, Ingela; Horn, Anna Catharina; Horn, Anna Catharina; Imer, Lisbeth M.; Johansson, Karl G.; Johansson, Karl G.; Niskanen, Samu; Palumbo, Alessandro; Richter, Anna Katharina; Rikhardsdottir, Sif; Rösli, Lukas; et al. (Modes of Modification, 2021)
The book highlights aspects of mediality and materiality in the dissemination and distribution of texts in the Scandinavian Middle Ages important for achieving a general understanding of the emerging literate culture. In nine chapters various types of texts represented in different media and in a range of materials are treated. The topics include two chapters on epigraphy, on lead amulets and stone monuments inscribed with runes and Roman letters. In four chapters aspects of the manuscript culture is discussed, the role of authorship and of the dissemination of Christian topics in translations. The appropriation of a Latin book culture in the vernaculars is treated as well as the adminstrative use of writing in charters. In the two final chapters topics related to the emerging print culture in early post-medieval manuscripts and prints are discussed with a focus on reception. The range of topics will make the book relevant for scholars from all fields of medieval research as well as those interested in mediality and materiality in general.